Procurement in Infrastructure : What Does Theory Tell Us? - Estache, Antonio (2012)
Infrastructure has particular challenges in public procurement, because it is highly complex and customized and often requires economic, political and social considerations from a long time horizon. To deliver public infrastructure services to citizens or taxpayers, there are a series of decisions that governments have to make. The paper provides a minimum package of important economic theories that could guide governments to wise decision-making at each stage. Theory suggests that in general it would be a good option to contract out infrastructure to the private sector under high-powered incentive mechanisms, such as fixed-price contracts. However, this holds under certain conditions. Theory also shows that ownership should be aligned with the ultimate responsibility for or objective of infrastructure provision. Public and private ownership have different advantages and can deal with different problems. It is also shown that it would be a better option to integrate more than one public task (for example, investment and operation) into the same ownership, whether public or private, if they exhibit positive externalities.